As vivências no Programa Residência Pedagógica de Química: uma análise dos relatórios dos residentes no âmbito dos estágios supervisionados - PINTO, Bianca Correa (2020)
This work presents an analysis about the episodes experienced along the Supervised Internship occurred concomitantly with the Ministry of Education Pedagogical Residence Program. The present research was developed according to the theoretical-methodological perspective of social representations upon the conceptual assumptions by Freire (1996) that characterize a multidimensional perspective focused on the profile of teaching practice. For the analysis of the information obtained, three predetermined dimensions were created, aiming to establish categories that could organize the information collected, described through the experiences expressed in the reports produced by the residents of Chemistry. In this direction, they were grouped in similarity and a greater number of citations and the most present in the reports according to the following formative dimensions: Planning and execution in the classroom, affective aspects and interpersonal relationships and reflections on professional constitution from the experiences of the internship. The results obtained express that the subjects share similar meanings about memorable experiences through the reality faced in the school space. In this sense, the teaching program approached here allowed the Chemistry undergraduates the opportunity of linking theory to practice by approaching the supervised internship along with the actions developed in the school-field, favoring the teacher-to-be with the power of improvement in the professional formative process.